Report Cards: The Impact of Providing School and Child Test Scores on Educational Markets - Andrabi, Tahir; Das, Jishnu; Khwaja, Asim Ijaz (American Economic Review, 2017)
We study the impact of providing school report cards with test scores on subsequent test scores, prices, and enrollment in markets with multiple public and private providers. A randomly selected half of our sample villages (markets) received report cards. This increased test scores by 0.11 standard deviations, decreased private school fees by 17 percent, and increased primary enrollment by 4.5 percent. Heterogeneity in the treatment impact by initial school test scores is consistent with canonical models of asymmetric information. Information provision facilitates better comparisons across providers, and improves market efficiency and child welfare through higher test scores, higher enrollment, and lower fees. (JEL D83, H75, I21, I28, O15, O18)